Incidencia de la comunicación pública de la ciencia en la divulgación de los hallazgos del mal de chagas en el sector rural del cantón Chaguarpamba de la provincia de Loja, periodo 2010 - 2011.- Propuesta alternativa - Espinoza Benavides, Marvin Gerardo (2015)
This thesis has the character of: analytical, descriptive, explanatory and interpretative applied refine and affirm that allows preventive elements through the public communication of science. Main problem raised a questioning matrix as well: What is the impact of public communication of science to disseminate the findings on Chagas disease in rural areas of the Canton Chaguarpamba of the Province of Loja ?. Such questioning was based on questions derived, structurally allowed to background, form and scientific support to the continued systemic process, as follows: 1) What are the policies that will allow the social science communicators disseminate the findings of Chagas disease in rural areas of the Canton Chaguarpamba ?, 2) What role being played by social science communicators to disseminate the findings of Chagas disease in the rural sector of the Canton Chaguarpamba ?, 3) How the media contribute to the science of Chagas disease in the rural sector of the Canton Chaguarpamba?. The answers obtained by scientific rigor, were achieved through methods: scientific, inductive and deductive, that allowed collect consistent information obtained through direct observation, interviews with students, parents and teachers from schools in the canton Chaguarpamba; Likewise, valid information from experts, scholars in Chagas disease through the interview was obtained The information obtained and referred oriented, systematically facilitated and sustained study and testing of the specific research hypotheses, finding logical results, which ultimately provided the ideal stage to draw conclusions and recommendations, which helped to envision an alternative proposal, based on educomunicacionales preventive components court. For feasible to construct the proposed alternative information, we investigated in detail from the demographic and psychographic, from the scientific and technical relevant codes and suitable to the axes of syntagmatic and paradigmatic campaign, seeking above all the campaign specifically suits the jurisdiction studied, setting records diatopical variation diatrástica and diafástica as follows: a) BACKGROUND: This is the pretext surmised content, text, context and even meta-text, manifest in objects, supports and variants (OSP); and, b) FORM: To be investigated in detail experts campaigns, savvy texts, advertising and propaganda speeches, components supported on morphological, semantic, semiotic, narrative, etc .. Through statistical analysis conclusions that facilitated the rise of the composition amounted contextual and conceptual form, as Pantone color palettes and structural morphologies, graphic design, composition quadrants management, management of physical and digital media, applicable to charts, audiofónicos and audiovisual channels. Based on formulas as RIO communication and AIDA.